Let's cook French : a family cookbook = Cuisinos Français : un livre pour toute la famille - Pépin, Claudine (Quarry Books, 2015)
According to Jacques Pepin, "the moment for a child to be in the kitchen is from the moment they are born." Let's Cook French, written by his daughter Claudine Pepin, is a fun, interactive, bilingual cookbook for families that introduces the art and joy of French cooking. It teaches better eating habits and the importance of culture, while providing quality family bonding time. Featuring classic, simple dishes inspired by French cuisine, each recipe is shown in both French and English and accompanied by charming illustrations. With an emphasis on fresh ingredients and hands-on preparation, dishes include traditional starters, main courses, and desserts. Your child's creativity will be sparked, as will your deeper connection with them."Let's Cook French is a magical introduction to some of the most delicious French classics. With Claudine's recipes, her father's and her daughter's illustrations, this is a book by a family for your family." - Dana Cowin, Editor in Chief, FOOD & WINE"I cannot think of anyone more qualified to write a French cookbook for children than Claudine Pepin! A trusted television personality, accomplished cook, seasoned teacher, and dedicated mom, Claudine has spent her entire life learning from and cooking alongside the most renowned chefs in the world. Complete with countless personal stories, beautiful illustrations by her father and her daughter, and timeless recipes developed with her husband, Let's Cook French is an absolute delight for the whole family and a source of inspiration for aspiring chefs of all ages. Bravo!" - Gail Simmons, TV host and author of Talking With My Mouth Full"If there's one thing I've learned from the French, it's that good cooking is not an end in itself. Rather, it's the crucial thing that brings the family together for a meal at the end of every day - and nothing's more important than that. Claudine Pepin, Jacques's daughter, was schooled in this lesson from birth. Now she is paying it forward. Simply but clearly written, and vivid with illustrations that recall the "Madeleine" books, "Let's Cook French" is seductive. If anyone can tempt kids away from nuggets and pizza, into the kitchen, and on to the dinner table, it's Claudine." - Sara Moulton of Sara's Weeknight Meals"My dear friends, Claudine and her father Jacques Pépin, have taught America to love French cooking. Now, with this very special book, these two amazing storytellers have shared their passion for family, fun and good food with a new generation of cooks. Claudine's recipes open a window into the flavors of France, and Jacques astonishing drawings will inspire children to be hungry for more!" - Jose Andres, internationally acclaimed chef, author, educator, and owner of ThinkFoodGroup